2022
DOI: 10.3390/ijms232213784
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Inhibitors for the Treatment of Recurrent and Unresectable Bone Sarcomas

Abstract: Bone sarcomas are a heterogeneous group of rare tumors with a predominance in the young population. Few options of systemic treatment are available once they become unresectable and resistant to conventional chemotherapy. A better knowledge of the key role that tyrosine kinase receptors (VEGFR, RET, MET, AXL, PDGFR, KIT, FGFR, IGF-1R) may play in the pathogenesis of these tumors has led to the development of multi-target inhibitors (TKIs) that are progressively being incorporated into our therapeutic arsenal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 128 publications
0
12
0
Order By: Relevance
“…Cabozantinib targets VEGFR1/2/3, PDGFR, KIT, MET, RET, and AXL; it also demonstrated preclinical antitumor activity against OS. This TKI enhanced OS cell migration and proliferation via the ERK/AKT signaling pathways [ 58 ]. In clinical trials, cabozantinib increased the PFS to ~7 months [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabozantinib targets VEGFR1/2/3, PDGFR, KIT, MET, RET, and AXL; it also demonstrated preclinical antitumor activity against OS. This TKI enhanced OS cell migration and proliferation via the ERK/AKT signaling pathways [ 58 ]. In clinical trials, cabozantinib increased the PFS to ~7 months [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This TKI enhanced OS cell migration and proliferation via the ERK/AKT signaling pathways [ 58 ]. In clinical trials, cabozantinib increased the PFS to ~7 months [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone sarcomas, dubious results were also observed. In OS, sorafenib treatment blocked cell proliferation and was able to reduce tumor growth in murine models [ 820 , 821 , 822 ]. However, other studies showed that sorafenib was only able to reduce tumor growth when combined with everolimus, or palbociclib, probably due to the capacity of sorafenib to induce mTORC activation [ 821 , 823 ].…”
Section: Kinases As Druggable Targets—evidence and Limitationsmentioning
confidence: 99%
“…For all these trials, there are only two main types of OS: soft and solid, as observed in the table. The following active pharmaceutical ingredients (API) are appropriate for OS: topotecan (Tpt) [45], pazopanib (Pzp) [46], placebo (Plb) [47], gemcitabine (Gct) [48], M6620 [49][50], regorafenib (Rgf) [51][52], glembatumumab vedotin (GV) [53][54], lenvatinib [55], etoposide and ifosfamide (EnI) [56], nab-rapamycin (Rpm) [57][58], cyclophosphamide (Cfa) [59], simvastatin (Sim) [60], myeloid growth factor (MGF) [61], nab-paclitaxel [62][63], methotrexate (Mtx) [64], and doxorubicin (Dox) [65]. Besides, the primary tests, such as laboratory biomarker analyses [66] and dose escalation studies [67], were conducted for these successful triumphs.…”
Section: Clinical Advancementmentioning
confidence: 99%